482 views
0 votes
Three questions, 38 points

simplify the first picture


second question

simplify the second picture

third question

simplify the third picture

Three questions, 38 points simplify the first picture second question simplify the-example-1
Three questions, 38 points simplify the first picture second question simplify the-example-1
Three questions, 38 points simplify the first picture second question simplify the-example-2
Three questions, 38 points simplify the first picture second question simplify the-example-3
User BalusC
by
5.3k points

1 Answer

6 votes

The rules of exponents that apply here are ...


a^(b)\cdot a^(c)=a^((b+c))\\a^(-b)=(1)/(a^b)\\ \left(a^(b)\right)^(c)=a^((b\cdot c))

1.


\displaystyle \left((4^(7))/(5^(2))\right)^(3)=(4^((7\cdot 3)))/(5^((2\cdot 3)))\\\\=(4^(21))/(5^(6))

2.


\displaystyle (9^(2))/(9^(7))=9^((2-7))=9^(-5)\\\\=(1)/(9^5)

3.


\displaystyle (6^(-3))/(6^(5))=6^((-3-5))=6^(-8)\\\\=(1)/(6^8)

User BhavikKama
by
5.6k points